Methodological Aspects of Social and Economic Efficiency of the Regional Activities - SANDU, Ivan Stepanovich; VESELOVSKY, Mikhail Yakovlevich; SEMYONOVA, Elena Ivanovna; FEDOTOV, Alexander Vladlenovich; DOSHCHANOVA, Alma Irgibaevna (Journal of Advanced Research in Law and Economics; Vol 6 No 3 (2015): JARLE Volume VI, Issue 3(13), Winter 2015, 2017)
The article reviews the main approaches to determine the efficiency of the regional level through the system of indicators adopted by the Federal Statistics Service in regard to a certain limit, using the particular indicators. The proposed methodology of evaluation of the social and economic efficiency is based on a comparison of regions by economic and social indicators of blocks, calculation of the index for each block and the formation of a comprehensive integrated assessment of economic and social development of the subjects of the Russian Federation. Its approbation by the Russian Federation and the Moscow region indicates a growing social and economic efficiency.